2022
DOI: 10.3390/molecules27134266
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry Ethanol Extract and Rutin Protect Alcohol-Damaged GES-1 Cells by Inhibiting the MAPK Pathway

Abstract: Mulberry extract has been proven to have the effect of resisting alcohol damage, but its mechanism is still unclear. In this study, the composition of mulberry ethanol extract (MBE) was identified by LC-MS/MS and the main components of MBE were ascertained by measuring. Gastric mucosal epithelial (GES-1) cells were used to elucidate the mechanism of MBE and rutin (the central part of MBE) helped protect against alcohol damage. The results revealed that phenolics accounted for the majority of MBE, accounting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Results showed that cell viability in the ulcer model group (27.16%) (P < 0.001) was significantly reduced relative to the control group. Pretreatment with DOFF at 80 μg/mL (33.9%), 160 μg/mL (50.4%), and 320 μg/mL (61.7%) remarkably improved decrease in cell viability compared with the model group, which was consistent with prior reports [63]. The best effect observed at a dose of 320 μg/mL was thus selected for further in vitro assays.…”
Section: Doff Modulates Ges-1 Cell Apoptosis Via Ros-dependent Pathwaysupporting
confidence: 88%
“…Results showed that cell viability in the ulcer model group (27.16%) (P < 0.001) was significantly reduced relative to the control group. Pretreatment with DOFF at 80 μg/mL (33.9%), 160 μg/mL (50.4%), and 320 μg/mL (61.7%) remarkably improved decrease in cell viability compared with the model group, which was consistent with prior reports [63]. The best effect observed at a dose of 320 μg/mL was thus selected for further in vitro assays.…”
Section: Doff Modulates Ges-1 Cell Apoptosis Via Ros-dependent Pathwaysupporting
confidence: 88%
“…Direct observation of cell status is helpful for preliminary judgment of screening concentration. A study demonstrated that the cell survival rate was approximately 50% after exposure to 3% ethanol for a duration of 4 h ( 33 ). Furthermore, the study outlined the recommended concentration (2–8%) and duration (2–6 h) to minimize volatilization in ethanol molding ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study demonstrated that the cell survival rate was approximately 50% after exposure to 3% ethanol for a duration of 4 h ( 33 ). Furthermore, the study outlined the recommended concentration (2–8%) and duration (2–6 h) to minimize volatilization in ethanol molding ( 33 ). In this study, ethanol treatment for 2 h and the cell survival rate of about 60% was used as modeling criteria to explore the optimal concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [60] demonstrated that mulberry ethanol extract (MBE) and rutin (the most abundant phenolic component in MBE) signifcantly reduced the expression of several genes mediating the MAPK pathway, including ERK, JNK, p38, and caspase-3, leading to reduced oxidative stress in gastric mucosal epithelial cells. Tis was done using the quantitative PCR method.…”
Section: Discussionmentioning
confidence: 99%